A Cost‐Effectiveness Analysis of Nivolumab and Ipilimumab Versus Sunitinib in First‐Line Intermediate‐ to Poor‐Risk Advanced Renal Cell Carcinoma. (1st February 2019) - Reinhorn, Daniel; Sarfaty, Michal; Leshno, Moshe; Moore, Assaf; Neiman, Victoria; Rosenbaum, Eli; Goldstein, Daniel A.
Abstract: Background: The treatment paradigm of advanced renal cell carcinoma (RCC) has changed rapidly in recent years. In first‐line treatment of intermediate‐ to poor‐risk patients, the CheckMate 214 study demonstrated a significant survival advantage for nivolumab and ipilimumab versus sunitinib. The high cost of combined immune‐modulating agents warrants an understanding of the combination's value by considering both efficacy and cost. The objective of this study was to estimate the cost‐effectiveness of nivolumab and ipilimumab compared with sunitinib for first‐line treatment of intermediate‐ to poor‐risk advanced RCC from the U.S. payer perspective. Materials and Methods: A Markov model was developed to compare the costs and effectiveness of nivolumab and ipilimumab with those of sunitinib in the first‐line treatment of intermediate‐ to poor‐risk advanced RCC. Health outcomes were measured in life‐years and quality‐adjusted life‐years (QALYs). Drug costs were based on Medicare reimbursement rates in 2017. We extrapolated survival beyond the trial closure using Weibull distribution. Model robustness was addressed in univariable and probabilistic sensitivity analyses. Results: The total mean cost per‐patient of nivolumab and ipilimumab versus sunitinib was $292, 308 and $169, 287, respectfully. Nivolumab and ipilimumab generated a gain of 0.978 QALYs over sunitinib. The incremental cost‐effectiveness ratio (ICER) for nivolumab and ipilimumab was $125, 739/QALY versus sunitinib. Conclusion: Our analysis established that the base case ICER in the model for nivolumab and ipilimumab versus sunitinib is below what some would consider the upper limit of the theoretical willingness‐to‐pay threshold in the U.S. ($150, 000/QALY) and is thus estimated to be cost‐effective. Implications for Practice: This article assessed the cost‐effectiveness of nivolumab and ipilimumab versus sunitinib for treatment of patients with intermediate‐ to poor‐risk metastatic kidney cancer, from the U.S. payer perspective. It would cost $125, 739 to gain 1 quality‐adjusted life‐year with nivolumab and ipilimumab versus sunitinib in these patients. Abstract : The treatment paradigm of advanced renal cell carcinoma (RCC) has changed rapidly in recent years. This article reports on the cost‐effectiveness of nivolumab and ipilimumab compared with sunitinib for first‐line treatment of poor‐ to intermediate‐risk advanced RCC from the U.S. payer perspective.